Impact of Environmental Regulation on High-Quality Economic Development - Ma, Xiaowei; Xu, Junwei (Frontiers in Environmental Science, 2022)
Based on the connotation of high-quality economic development (HQED) in China, this study uses panel data of 30 provinces (cities and regions) in China from 2005 to 2019 to construct an evaluation index system of HQED with three dimensions of "economic development - social life - ecological environment", and establishes a fuzzy comprehensive evaluation model to calculate the HQED index. The results show that the high-quality development level of China's economy shows an upward trend of fluctuation, but the development level is still low and there are obvious regional differences. The eastern region enjoys the highest level of HQED, followed by the central region and western region. The panel data regression model is further established to analyze the impact of environmental regulation on economic development. It is found that there is an inverted u-shaped relationship between environmental regulation and HQED, and there is a "cost compliance" effect between environmental regulation and quantitative economic development. Strict environmental regulation measures will inhibit economic quantity growth. The results of heterogeneity analysis show that environmental regulation has different impacts on the economic development of the three regions due to the differences in resource endowment. The influence of environmental regulation on economic development in eastern China is similar to that in the whole country. However, in the central region, there is an "innovation compensation" effect between environmental regulation and HQED, and a "U" shape relationship between environmental regulation and quantitative economic development. In western China, the enhancement of environmental regulation will inhibit high-quality and quantitative economic development.